2016
DOI: 10.1364/ol.41.001817
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-enhanced coherent-illumination phase diversity for phase retrieval in coherent imaging systems

Abstract: We propose a phase-retrieval method based on the numerical optimization of a new objective function using coherent phase-diversity images as inputs for the characterization of aberrations in coherent imaging systems. By employing a spatial light modulator to generate multiple-order spiral phase masks as diversities, we obtain an increase in the accuracy of the retrieved phase compared with similar state-of-the-art phase-retrieval techniques that use the same number of input images. We present simulations that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, the performed simulations indicate that engineered PSFs are inferior when an entire set, i.e., N = 7, of aberrations is measured for an extended scene. We note that other authors claim to have found PE PSF designs with a superior performance [46,47] in comparison with the conventional PSF. However, the results of the corresponding analyses are limited.…”
Section: B Crlb Performancementioning
confidence: 57%
See 1 more Smart Citation
“…However, the performed simulations indicate that engineered PSFs are inferior when an entire set, i.e., N = 7, of aberrations is measured for an extended scene. We note that other authors claim to have found PE PSF designs with a superior performance [46,47] in comparison with the conventional PSF. However, the results of the corresponding analyses are limited.…”
Section: B Crlb Performancementioning
confidence: 57%
“…First, the simulations in Refs. [46,47] consider only idealized point sources. On the other hand, the calculation is performed for only a single, non-optimized diversity value 4 .…”
Section: B Crlb Performancementioning
confidence: 99%
“…The methodology described is a way to prove how the aberrations were correctly found, because if the object complex field is known the error of its reconstruction should be low as it was shown in the simulations. In this sense, new iterative methods have been developed with very little error for this purpose [30].…”
Section: B Experimentalmentioning
confidence: 99%